Activated AMP-activated protein kinase prevents hepatic steatosis, oxidative stress and inflammation in primary chicken hepatocytes - Yao, Yao; Li, Longlong; Wang, Huihui; Yang, Ying; Ma, Haitian (Frontiers in Physiology, 2022)
Fatty liver hemorrhagic syndrome (FLHS) in laying hens, a nutritional metabolic disorder disease, can lead to the decline of laying rate, shortening of laying peak period and increase of mortality, which seriously constrain the sustainable development of layer industry. Until now, there is no effective strategies can prevent and control the occurrence of fatty liver hemorrhagic syndrome in laying hens. The AMP-activated protein kinase (AMPK), a major sensor of cellular energy status, acts a crucial role in regulating lipid metabolism, oxidative stress and inflammatory responses in body. However, the potential molecular mechanisms about AMP-activated protein kinase signal in controlling the occurrence of fatty liver hemorrhagic syndrome are remain unclear. In present study, we found that the phosphorylated AMP-activated protein kinase (Thr172) protein level was markedly reduced in palmitic acid plus oleic acid (PO)-induced primary chicken hepatocytes. Moreover, blocked AMP-activated protein kinase signal by AMP-activated protein kinase inhibitor compound C obviously exacerbated lipid metabolism disorders, oxidative stress and inflammatory response triggered by palmitic acid plus oleic acid in primary chicken hepatocytes. Nevertheless, the lipid metabolism disorders, oxidative stress and inflammatory response challenged by palmitic acid plus oleic acid were obviously alleviated through activation of AMP-activated protein kinase signal with AMP-activated protein kinase activator AICAR in hepatocytes. In addition, we found that the beneficial effects of AMP-activated protein kinase signal in relieving lipid metabolism disorders, oxidative stress and inflammatory response are achieved by activating the nuclear factor erythroid 2-related factor 2 (NRF-2)/kelch-like ECH-associated protein 1 (KEAP1) pathway and inhibiting the NF-κB pathway in PO-stimulated primary chicken hepatocytes. Collectively, our data demonstrated that AMP-activated protein kinase acts as a potential target for the prevention of fatty liver hemorrhagic syndrome occurrence in laying hens.